The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5402/2013/604045
|View full text |Cite
|
Sign up to set email alerts
|

Lipids in Marine Ecosystems

Abstract: Lipids provide the densest form of energy in marine ecosystems. They are also a solvent and absorption carrier for organic contaminants and thus can be drivers of pollutant bioaccumulation. Among the lipids, certain essential fatty acids and sterols are considered to be important determinants of ecosystem health and stability. Fatty acids and sterols are also susceptible to oxidative damage leading to cytotoxicity and a decrease in membrane fluidity. The physical characteristics of biological membranes can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
199
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(232 citation statements)
references
References 120 publications
2
199
0
3
Order By: Relevance
“…The metabolites responsible for most of the observed variance in PCA analysis were shown to be lipids. We propose that this difference may be due to the different temperatures at the varied sampling sites (B10 1C to B30 1C across the latitudinal gradient) (Parrish, 2013). Once the influence of the lipids were removed from the analysis, or focusing on samples from single regions, a strong species-specific component was revealed that was due largely to secondary metabolism ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolites responsible for most of the observed variance in PCA analysis were shown to be lipids. We propose that this difference may be due to the different temperatures at the varied sampling sites (B10 1C to B30 1C across the latitudinal gradient) (Parrish, 2013). Once the influence of the lipids were removed from the analysis, or focusing on samples from single regions, a strong species-specific component was revealed that was due largely to secondary metabolism ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Three major clusters are formed comprising California, Florida and a combination of Papua New Guinea and Vanuatu in a single cluster. We hypothesized that this pattern was due to lipids in the extracts, which likely vary, because different temperatures would require different components to maintain membrane fluidity (Parrish, 2013). Alternatively, it might be due to other effects, such as available food sources, although this seemed less likely due to the large geographical sampling range in the tropical Pacific.…”
Section: Bioactivity Profile Of Ascidian Chemical Extractsmentioning
confidence: 99%
“…the C 20 PUFA, A RA and EPA, were more to xic than the C 18 PUFA octadecatetraenoic acid (OTA, 18:4ω -3). Since ARA and OTA have the same number of double bonds, and ARA is more to xic than EPA, the degree of unsaturation does not seem to be a key determinant of toxicity level (Parrish 2013).EPA with 2% and DHA with 3% were the t wo PUFA mainly detected in April, 2012. Fatty acid co mposition of algal lipids varies widely with species, habitat, light, salinity, pollution and environmental conditions (Kim et al, 1996;Ratana-Arporn and Chirapart, 2006) and in most studies 16:0 is predominant (Khotimchenko et al, 2002;Li et al, 2002;Gressler et al, 2010;Leblond et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The physical characteristics of biological membranes can be defended from the influence of changing temperature, pressure, or lip id pero xidation by altering the fatty acid and sterol composition of the lipid bilayer. Th e influence of essential lipids, lipid o xidation, and memb rane composition on food web structure and function will become increasingly important in the context of global warming and ozone deplet ion (Parrish, 2013). In the present study, the biochemical parameters as fatty acids, sterols and lipophilic vitamins have been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid content and fatty acid profile of C. euxinus is extremely important in the sustainability of Black Sea anchovy that has an important place in Turkey's fisheries. Because, among the lipids, certain essential fatty acids are considered to be important determinants of ecosystem health and stability (Parrish, 2013). Also, fatty acids provide versatile signatures that are being increasingly employed to delineate the transfer of dietary material through marine and terrestrial food webs (Parrish et al, 2015).…”
Section: Fatty Acid Profilementioning
confidence: 99%